Respon Non Linier Sifat Optis Larutan MgSO4 - Firdausi, K. Sofjan; Azam, Much.; Romadhona, Thithit; Abadi, Prayitno (BERKALA FISIKA, 2006)
A response of nonlinear optic of several salt solutions in external magnetic field has been studied. An altered magnetic field varies from 0 until 0,2T used to induce samples, and then change of polarization angle b is measured by polarizators, where the direction propagation of laser is perpendicular to the direction of B. Various concentration of solution is used at 5% until 35%. Our experiment shows that the graphs of b vs. B are still linear for mineral water and NaCl solution. However, for MgSO4 solution, we obtained polynomial tendency of this graph. At 20% until 35% of concentration of this solution it has polynomial in third order. Keywords: Nonlinear optics, change of polarization angle, external magnetic field.